The Effects of Apologies for Service Failures in the Global Online Retail. Issue 3 (3rd July 2018) - Sengupta, Sanchayan; Ray, Daniel; Trendel, Olivier; Vaerenbergh, Yves Van
ABSTRACT: Virtually all sources on service recovery stress the importance of offering an apology to complaining customers. To date, however, our understanding of who should offer the apology and how to offer the apology is still limited. Taking a cross-cultural perspective, Study 1 shows that Eastern customers attach more value to a manager (vis-à-vis a frontline employee) offering an apology than Western customers in an offline retailing context, but not in an online retailing context. In an online setting, Study 2 further extends these insights by showing that the status of service personnel matters for Eastern customers, but only if the apology is provided publicly on social media and not if the apology is provided online privately. Global e-commerce managers can benefit from these findings when developing their service recovery strategies. By demonstrating that recovery strategies that are proposed and tested in offline settings are non transferrable to online settings, this article provides a clearer understanding of service recovery across online and offline channels. Based on face theory, this research highlights the public versus private nature of an apology in a global online retailing context, thus contributing to the emerging research in online service recovery.